Current Individual and Retrospective Factors Associated with Lifelong Learning among 50-64 Year Olds in the Baltic States - Zamalijeva, Olga; Kairys, Antanas; Miķelsone, Madara; Reine, Ieva (Pedagogika, 2023)
This research is aimed to analyse the role of current and retrospective factors in participation in educational and training courses among 50-64year-old adults from the Baltic states. A sample of 3448 working age adults was drawn from SHARE wave 7 database Analysis shows significant cross-country differences with the highest proportion of attendance in Estonia. Participation is related to personality traits, being active in the labour market, education level and some retrospective factors.